Pineapple Prebiotics for Osteoblast Viability and Periodontitis Antibacterial Therapy - Indrawati, Dwi Wahyu; Mariyati, Lely Ika; Mukti, Ria Andriani; Zakyzein, Mochammad Alfahrizhy (Universitas Padjadjaran, 2025)
Periodontitis is a chronic inflammatory disease that progressively damages periodontal supporting tissues as a result of colonization by pathogenic bacteria, especially Porphyromonas gingivalis. This condition is characterized by gingival inflammation, loss of periodontal ligament, and resorption of alveolar bone. Conventional therapy through scaling, root planing, and systemic antibiotics is frequently limited by bacterial resistance, relapse, and potential adverse effects. Therefore, alternative natural agents that are safe and able to support bone regeneration are highly required. This study aimed to evaluate the antibacterial activity as well as the biological effect of pineapple (Ananas comosus) prebiotic extract on osteoblast viability. An in vitro experimental design was applied using disc diffusion assays to measure inhibition zones against P. gingivalis and MTT assays to evaluate osteoblast viability. Fermented extracts at concentrations of 10%, 20%, and 30% were tested, with metronidazole as a positive control. Results showed concentration-dependent increases in inhibition zones, namely 7.9 mm (10%), 10.42 mm (20%), and 13.22 mm (30%). MTT assays demonstrated enhanced osteoblast viability at 10% (0.534) and 20% (0.600), whereas viability decreased at 30% (0.551), suggesting possible cytotoxicity at higher doses. ANOVA indicated significant differences among groups (p < 0.05). In conclusion, pineapple prebiotic extract exhibits dual therapeutic potential: antibacterial activity against P. gingivalis and stimulation of osteoblast viability, supporting its development as a promising adjuvant therapy for periodontitis with infection control and alveolar bone regeneration benefits. Keywords: Antibacterial, bromelain, pineapple, osteoblast, periodontitis.